Accumulating and Utilizing Intellectual Capital: Chinese International Students’ Post-Graduation Career Strategies (Comparative & International Education Series, 2022)
As the United States faces the crisis of recruiting and retaining Chinese international students, in this chapter, I investigate Chinese international students’ post-graduation career challenges and strategies. Findings showed that while Chinese international students were confronted with obstacles in landing a job with visa sponsorship in the US, the competition to find employment was also intense in China. In responding to these career challenges, Chinese international students employed strategies including (a) maximizing or minimizing their stay in the US, (b) pursuing a higher-level US degree, and (c) seeking transnational careers. All of these strategies served to accumulate and utilize their intellectual capital for the best career outcomes. This study emphasized the importance for American higher education to better facilitate international students’ post-graduation career success.How to cite in APA:Li, X. (2022). Accumulating and utilizing intellectual capital: Chinese international students’ post-graduation career strategies. In X. Zhao, M. Kung, K. Bista, & Y. Ma (eds), Home and abroad: International student experiences and graduate employability (pp. 163-175). STAR Scholars.[order hardcopy ]